Mineral dust and lead deposition from land use and metallurgy in a 4800-year-old peat record from the Central Alps (Tyrol, Austria) - Scheffer, Clemens von; De Vleeschouwer, François; Le Roux, Gaël; Unkel, Ingmar (Quaternary international, 2024)
Humans have occupied the Alps over most of the Holocene. Yet, continuous records on the impact of using montane resources and landscapes are scarce or confined to segregated areas or periods. We present a high-resolution geochemical record of the last 4800 years from the ombrotrophic peatland Piller Moor in the Central Alps (Tyrolean Oberland, western Austria), using inductively coupled mass plasma spectrometry (ICP-MS) and highly efficient inter-calibrated portable X-ray fluorescence analysis (pXRF). Fluctuations of metal enrichment factors (EF) for lead (Pb), copper (Cu), zinc (Zn) and antimony (Sb), accumulation rates of anthropogenic lead (Pbanth AR) and mineral matter (MAR), based on titanium (Ti), are in line with archaeological and pollen evidence for human presence and environmental change. Periods of intensified, erosive land use are indicated by MAR around 4400 cal BP, 3400 cal BP and, very prominently, at 2400 cal BP. After low MAR in the early Middle Ages, soil disturbances reappear around 1200 cal BP (750 AD), after 200 cal BP (1750 AD) and during the 20th century AD. We found evidence that metallurgy was practised in the area as early as 4450 cal BP, again from 3500 to 2900 cal BP and episodically between 2400 and 1400 cal BP. The Central Alps were presumably a source of increased Pb-emissions in the post-Roman period from 1500 to 1400 cal BP (450-550 AD). Generally, our findings suggest that mining predates archaeological and historical evidence. Following a continuous increase since the Middle Ages, atmospheric Pb EF and Pbanth AR peak around 1980 AD. The record of mineral atmospheric input illustrates the notable impact of human activities on soil erosion and dust entrainment in the Central Alps. Furthermore, links between Little Ice Age cold phases and reduced human impact and mining are established. Our high-resolution peat-geochemistry data quantifies atmospheric deposition of mineral matter and Pb, which act as proxies for landscape evolution and metallurgy on a local and regional scale. It provides new insights and a deeper understanding of the interaction of climate, environment and humans in mountainous landscapes like the Central Alps.